Optimalisasi Brand Identity dan Pemasaran Digital untuk Meningkatkan Omzet UMKM di Kampung Kue Rungkut Lor Surabaya - Yoga Adi Prayogi; Rangsang Purnama; Febryan Prima Saputra; Dian Suci Lestari; Adinda Putri Ayunda; Reva Wahyuning Tyas (Journal of Community Service and Engagement, 2026)
Kampung Kue Rungkut Lor, located in Kali Rungkut Village, Surabaya, is a center for micro, small, and medium enterprises (MSMEs) that produce a variety of traditional East Javanese cakes. Despite its great economic potential, most businesses in this village face challenges in terms of management, financial management, and the use of digital technology for product marketing. The Thematic Community Service Program (KKN) conducted by students from Bhayangkara University Surabaya aims to provide practical training in business management, basic financial literacy, and the application of digital marketing to enhance the brand identity and market reach of Kampung Kue's SMEs. This program involves various training sessions such as “Buku Kecil Cuan” (Small Book of Profit) for financial literacy and “Foto Cuan & Storytelling Visual” (Profit Photos & Visual Storytelling) to improve branding and digital content creation skills. In addition, digital marketing assistance focused on optimizing the use of marketplaces and social media aims to increase sales turnover. Evaluation was carried out by measuring the increase in participants' knowledge through pre-tests and post-tests as well as measuring turnover results before and after program implementation. The results of the activity show an increase in the community's understanding of financial management and digital marketing, which has led to an increase in MSME sales turnover. This program is expected to become a model that can be replicated in other villages with similar potential.